(untitled) (Journal of Biomedical Investigation, 2024)
Background: Fusarium species infection is on the increase leading to morbidity and mortality in immunocompromised hosts. There have been several reports of disseminated infection of Fusarium species in immunosuppressed patients over the last 25-30 years. Aim: The study aimed to determine the histopathological impact of the isolated Fusarium solani on the histomorphology of brain, liver and spleen tissue of albino mice. Material and Methods: Isolates of Fusarium solani from humans and plants were obtained from clinical samples of patients and different plant products respectively. All the samples collected, were cultured immediately on Sabouraud Dextrose Agar slant containing 50 mg/l of chloramphenicol and 5 mg/l of gentamicin. Identification of isolates was carried out macroscopically and microscopically using standard mycological methods. Test mice were challenged with isolated conidia of Fusarium solani while the control mice were unexposed. After 30 days, randomly chosen surviving test mice and control were sacrificed. The brain, liver and spleen of the animals were aseptically excised for tissue burden estimation and further histological processing for light microscopical examination. Result: In vivo virulence studies of Fusarium solani on mice brain, liver and spleen organs revealed disseminated infection of multiple organs and mortality. The presence of fungal propagules was detected in all organs, with the highest concentration found in the spleen. There were intense inflammations of the internal organs especially excretory organs compared to the control where there was no inflammation seen. Histopathological findings on the brain showed extensive oedemas with blurring of the white and grey matter junction and extensive destruction of the Purkinje cells. Splenic tissues also revealed complete destruction of the splenic bulb and presence of extensive destructive granulomas with many Langhans giant cells formed. There was also evidence of infections in the liver tissue ranging from intense hepatocyte swelling with hyperchromatic nuclei to intense periportal mononuclear cell infiltrates arising from diffuse toxic hepatic injury. Conclusion: This study showed strong evidence of Fusarium solani pathogenicity in mice from various pathological manifestations and physical signs observed.